2017
DOI: 10.1016/s2214-109x(17)30205-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Xpert MTB/RIF for tuberculosis diagnosis in South Africa: a real-world cost analysis and economic evaluation

Abstract: SummaryBackgroundIn 2010 a new diagnostic test for tuberculosis, Xpert MTB/RIF, received a conditional programmatic recommendation from WHO. Several model-based economic evaluations predicted that Xpert would be cost-effective across sub-Saharan Africa. We investigated the cost-effectiveness of Xpert in the real world during national roll-out in South Africa.MethodsFor this real-world cost analysis and economic evaluation, we applied extensive primary cost and patient event data from the XTEND study, a pragmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 29 publications
2
61
1
1
Order By: Relevance
“…To assess validity of our unit cost estimates, we compared our results with previously published estimates of TB diagnostics and interventions. [16,[24][25][26][27] Focusing on cost per Xpert test, we find our estimates consistent and comparable to the existing evidence (between $12 and $42 per test) factoring operational settings, costing methods, consumables costs, and testing volumes. In comparing our cost per program yield estimates, we found one study that reported costs of program operation and yields of the CATA program that overleaped with our assessment period but reporting much lower cost estimate.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…To assess validity of our unit cost estimates, we compared our results with previously published estimates of TB diagnostics and interventions. [16,[24][25][26][27] Focusing on cost per Xpert test, we find our estimates consistent and comparable to the existing evidence (between $12 and $42 per test) factoring operational settings, costing methods, consumables costs, and testing volumes. In comparing our cost per program yield estimates, we found one study that reported costs of program operation and yields of the CATA program that overleaped with our assessment period but reporting much lower cost estimate.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, we were not able to capture uncertainties in cost estimates that may arise due to variabilities in operations and workloads that may depend on operational settings conditions. [24,26,30] This limitation can be overcome by designing costing studies alongside the program development and implementation to include staff timeuse surveys or time and motion and tracking operational statistics so that these data can help inform cost allocation mechanisms, describe uncertainties in cost estimates associated with operational variabilities and activity-specific inefficiencies [24,31]. Subsequently, we recommend that costs be routinely evaluated so that variability in operations and settings can be captured and reflected as part of the cost reports.…”
Section: Limitationsmentioning
confidence: 99%
“…Xpert was superior over microscopic determination of drug susceptibility (MODS) in high TB/HIV prevalence setting (18). Whereas, Vassall et al (19) reported that Xpert was cost-neutral and did not improve the cost-effectiveness of TB diagnosis in South Africa. Budgetary constraint is a major consideration influencing the choice of diagnostics in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…This includes a careful assessment of acceptability and feasibility linked to possible increased stresses on the health system/provider when testing is introduced into settings where thus far no or limited testing was performed. Studies using the GeneXpert MTB/RIF TB test showed that new diagnostic tests would not have the expected impact on outcomes if test introduction is not accompanied by changes in patient pathways or practices 72,73 . These studies highlight the importance of programmatic monitoring of the impact of novel technologies beyond studies that are usually conducted under controlled conditions.…”
Section: Factors Associated With Successful Assured Diagnosticsmentioning
confidence: 99%